Amino acid digestibility and metabolisable energy of spring and winter faba beans grown on two sites and effects of dehulling in caecectomised laying hens. (24th July 2021) - Siegert, Wolfgang; Ibrahim, Ahmad; Link, Wolfgang; Lux, Guido; Schmidtke, Knut; Hartung, Jens; Nautscher, Nadine; Rodehutscord, Markus
Abstract: BACKGROUND: The variation in amino acid (AA) digestibility and metabolisable energy (MEN ) in four spring and four winter faba bean genotypes differing in vicine/convicine (V/C) concentrations grown on two sites was investigated in caecectomised LSL‐Classic laying hens. Effects of dehulling one faba bean genotype were also examined. Diets containing one out of 17 faba bean variants each and a basal diet were fed to ten caecectomised laying hens in a row‐column design to achieve five replicates per diet. RESULTS: Ranges and levels of digestibility of the hulled variants differed widely among AA with the lowest and highest range determined for Arg (90–93%) and Cys (−12–65%), respectively. MEN ranged between 10.3 and 12.3 MJ kg −1 dry matter. Lower MEN and digestibility of Cys, Glx, Phe, Pro, Tyr, and Val ( P < 0.050) was determined for the winter genotypes grown in Nimtitz compared to the other variants. Digestibility of Ser was lower for the spring than for the winter genotypes ( P < 0.050). Negative correlations with AA digestibility were determined for phytate, but not for tannin and V/C concentrations ( P < 0.050). Negative correlations between tannin fractions and MEN were weak ( P = 0.082–0.099). Dehulling increased MEN by 1.8 MJ kg −1 dry matter and raised the digestibility of Pro, His, and Glx ( P < 0.050). CONCLUSIONS: The results indicated that the digestible AA and MEN supply of laying hens was increased by using low phytate faba beans while breeding for low V/C genotypes did not affect AA digestibility or MEN . Dehulling increased MEN and the digestibility of some AA. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.